The relationship of trait-like compassion with epigenetic aging: The population-based prospective Young Finns Study - Dobewall, Henrik; Keltikangas-Järvinen, Liisa; Marttila, Saara; Mishra, Pashupati P.; Saarinen, Aino; Cloninger, C. Robert; Zwir, Igor; Kähönen, Mika; Hurme, Mikko; Raitakari, Olli; Lehtimäki, Terho; Hintsanen, Mirka (Frontiers in Psychiatry, 2023)
Helping others within and beyond the family has been related to living a healthy and long life. Compassion is a prosocial personality trait characterized by concern for another person who is suffering and the motivation to help. The current study examines whether epigenetic aging is a potential biological mechanism that explains the link between prosociality and longevity. We used data from the Young Finns Study that follows six birth-cohorts from age 3-18 to 19-49. Trait-like compassion for others was measured with the Temperament and Character Inventory in the years 1997 and 2001. Epigenetic age acceleration and telomere length were measured with five DNA methylation (DNAm) indicators (DNAmAgeHorvath, IEAA_Hannum, EEAA_Hannum, DNAmPhenoAge, and DNAmTL) based on blood drawn in 2011. We controlled for sex, socioeconomic status in childhood and adulthood, and body-mass index. An association between higher compassion in 1997 and a less accelerated DNAmPhenoAge, which builds on previous work on phenotypic aging, approached statistical significance in a sex-adjusted model (n=1030; b =-.34; p=.050). Compassion in 1997 predicted less accelerated epigenetic aging over and above the control variables (n=843; b=-.47; p =.016). There was no relationship between compassion in 2001 (n=1108/910) and any of the other four studied epigenetic aging indicators. High compassion for others might indeed influence whether an individual’s biological age is lower than their chronological age. The conducted robustness checks partially support this conclusion, yet cannot rule out that there might be a broader prosocial trait behind the findings. The observed associations are interesting but should be interpreted as weak requiring replication.